Penerapan Metode Tilawati dalam Pembelajaran Membaca Al-Quran di Pondok Sabilul Huda - Mohamad Nasirudin; Mazidatul Faizah; Salim Ashar; Mega Kirana Dewi (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2021)
Education is done so that someone gets an understanding of a science. Education also makes it easier for a person to adjust to the surrounding environment. In its implementation, education begins with an educator who is able to make the atmosphere of education communicative and enjoyable. The tilawati learning method has the following objectives: 1. The purpose of this program is to determine the application of the Tilawati method in learning to read the Al-Quran at the Sabilul Huda Islamic Boarding School. 2. As input in improving the quality of learning to read the Al-Qur`an. 3. As a motivator in improving the quality of learning to read the Al-Qur'an. The target audience for the Al-Quran learning activities using the tilawati method are students who have not been able to use the tilawati method at the Sabilul Huda Islamic Boarding School. This activity was carried out at Pondok Sabilul Huda with a total of about 6-7 people. This activity uses a teacher from one of the Koran teachers at the Sabilul Huda Islamic Boarding School who is more familiar with this method. The approach method for the implementation of community service activities in the PPM scheme includes the classical approach method. The approach method is used in learning activities in order to get used to reading, to facilitate mastery of rast songs. Through this training activity, it is hoped that it can solve the problems faced by the partners. The results of the training activity satisfaction response showed that students rated this training activity as very useful and enjoyable. However, the time is very short. The results of the Koran teacher skills assessment showed that 70% of the training participants had good skills when practicing the tilawati method. As many as 30% of the training participants were in the category with fairly good skills.